SKRINING FITOKIMIA DAN UJI DAYA HAMBAT EKTRAK DAUN JAHE MERAH (Zingiber officinale var rubrum) TERHADAP BAKTERI Staphylococcus Epidermidis DAN Escherichia Coli - Ibrahim, Annisa Humairah; Hasan, Hamsidar; Sy. Pakaya, Mahdalena (Jurusan Farmasi Universitas Negeri Gorontalo, 2021)
Infectious disease is one of the diseases caused by microbes, including bacteria. Staphylococcus epidermidis and Escherichia coli are gram-positive and gram-negative bacteria that cause infectious diseases. The selection of medicinal plants as an alternative solution is an effective way of reducing the resistance of bacteria. Based on the empirical data, herbal plants with antimicrobial potential are red ginger (Zingiber officinale var rubrum). This research aimed to determine the inhibition test on Staphylococcus Epidermidis and Escherichia coli due to phytochemical compounds contained in the leaves of red ginger which serve as an antibacterial. Through this experimental laboratory research, a crude drug was extracted using n-hexane, chloroform, ethyl acetate, and methanol solvent. The phytochemical screening results of n-hexane extract showed that red ginger leaves contain alkaloids and terpenoids; chloroform extract contains alkaloids, steroids, and tannins; ethyl acetate extract contains alkaloids, steroids, flavonoids, and tannins; and the methanol extract contains alkaloids, terpenoids, flavonoids, and tannins. Chloramphenicol and Dimethyl sulfoxide (DMSO) were used as the positive control and negative control respectively. Inhibition test results were obtained from the four n-hexane extracts, chloroform extracts, ethyl acetate extracts, and methanol extracts with three different concentrations.The results obtained the greatest inhibition against Staphylococcus Epidermidis bacteria, namely at a concentration of 20% chlorform extract of red ginger leaves as large as 18,90 mm. Meanwhile, the inhibition of Escherichia Coli is at a concentration of 20% n-hexane extract with an inhibitory power of 17,84 mm inhibition zone that is classified as a strong category to inhibit the growth of bacteria .The results of the One Way ANOVA data analysis (p less than 0.01) with a confidence level of 99%.